The Effect of Graphic Organizers on ELT Students’ Writing Quality - Erlik Widiyani Styati; Lulus Irawati (Indonesian Journal of EFL and Linguistics, 2020)
Graphic organizers are used in ELT classroom to help the students learn better. It refers to the way the students use graphic organizers in writing. The purpose of this study is to investigate the effect of graphic organizers on ELT students’ writing quality. This study was a quasi-experimental research design. The experimental group was taught by using graphic organizers. The control group was administered by using conventional strategy. The participants of the research were the second semester students of English Department, in one of the private universities in Madiun. The data were analyzed by utilizing independent t-test and one-way ANOVA based on the level of significance at .05. The result of the study shows that there is a significant difference between the mean scores of the students in the experimental and control groups. The students who are taught by using graphic organizers are better than the students who are taught using conventional strategy. The students in the experimental group perform better on writing quality in terms of content, vocabulary, and mechanics than those who do in the control group. It can be concluded that graphic organizers have a significant effect on ELT students’ writing quality. It is effective to be used in order to help the students write better. The students are successful in generating the ideas of writing and it can create a social community. We recommend for the future researchers to realize other various graphic organizer models into research.